Expression of interleukin 1-alpha, interleukin 6 and CD 10 in predicting recurrence of ameloblastoma / Nurhazwani Mohd Danil - Nurhazwani , Mohd Danil (2024)
Background: Ameloblastoma (AM) is a benign yet locally aggressive odontogenic tumour with a high post-treatment recurrence rate. Despite advances in surgical techniques, predicting recurrence remains a significant challenge. Recent literature suggests that specific cytokines and markers, such as interleukin 1-alpha (IL-1α), interleukin 6 (IL-6), and CD 10, might play a role in AM’s aggressive behaviour and recurrence. Objectives: The aim of this study is to evaluate the expression levels of IL-1α, IL-6 and CD 10 and compare their immunoprofile in non-recurrent and recurrent AM. This study also sought to determine the association between expression level of these markers with demographic and clinicopathological parameters in non-recurrent and recurrent AM. Methods: A descriptive cross-sectional study comprising of 42 cases were divided into 3 groups; 16 cases of conventional AM with no recurrence (AMNR), 13 cases of primary conventional AM with recurrence (PAMR), and 13 cases of recurrent ameloblastoma from the same patient (RAM) subjected to immunohistochemical staining for IL-1α, IL-6 and CD 10. A semiquantitative scoring, immunoreactive scoring (IRS) was used to evaluate the expression of IL-1α, IL-6 and CD 10 in non-recurrent and recurrent AM. The expression levels were then correlated with demographic and clinicopathological parameters. Results: There were no significant differences (p>0.05) in IL-1α, IL-6, or CD10 expression across all groups. IL-1α expression was significantly associated with histopathological subtype in AMNR (p=0.03) and PR (p=0.002). In the AMNR group, IL-6 expression was significantly associated with tumour side localization (p = 0.01). CD 10 showed significant correlation with tumour side localization (p=0.02) in PAMR, and subsites of tumour localization in PAMR (p=0.005) and RAM (p=0.002). Conclusions: We observed an upregulation of IL-6 expression in recurrent AM compared to non-recurrent AM, suggesting the potential of IL-6 in predicting recurrence of AM. Downregulation of IL-1α and CD-10 expression in recurrent AM compared to non-recurrent AM needs further investigation in order to identify their role.